Behavioral and physiological bases of attentional biases: Paradigms, participants, and stimuli - Daniela M. Pfabigan (Frontiers Research Topics, 2015)
Attentional biases (ABs) play a prominent role in the development and maintenance of clinically relevant symptoms of, for example, anxiety and depression. In particular, increased attentional orienting and preoccupation with biologically relevant and mood-congruent stimuli has been observed, suggesting that the visual-attentional system is overly sensitive towards threat cues and avoidant of cues of reward in these disorders. First, several experimental paradigms have been used to assess ABs, e.g., the dot probe task, the emotional stroop task, and the spatial cueing task amongst others. Yet, these paradigms are based on different theoretical backgrounds and target different stages of the attentional process. Thus, different paradigms provided converging as well as diverging evidence with regard to ABs. However, it is often not entirely clear to what extent this reflects real differences and commonalities, or is caused by differences in methodology. For example, behavioral reaction time data can only provide a snapshot of selective attention. Measuring event-related potentials, eye movements, or functional brain imaging data enables exploring the exact temporal and spatial dynamics of attentional processes. Moreover, neuroimaging data reveal specific cortical networks involved in directing attention toward a stimulus or disengaging from it. Second, ABs have been mainly discussed as symptoms of psychopathology, while results in healthy participants are still scarce; previous studies mostly compared extreme groups. However, a comprehensive theoretical and empirical account of ABs in psychopathology also requires a thorough account of ABs in the general healthy population. Moreover, the effect of gender, as an important contributing factor in processing of emotional stimuli, has also not been considered systematically in previous research. Third, a variety of stimuli has been used in the assessment of ABs. So far, mostly facial or word stimuli have been applied. However, in everyday life not only facial emotion recognition but also a fast evaluation of complex social situations is important to be effective in social interactions. Recent research started using more complex stimuli to raise ecological validity. However, the use of ecologically valid stimuli poses some methodological challenges and needs to be applied more systematically. The aim of this research topic is to integrate different paradigms and stimuli, addressing individuals from the whole range of the population continuum, and to apply different methodological approaches. It is intended to bring together expertise in stimulus selection, timing and implementing issues, advancing and broadening the overall understanding of ABs.